Ответ:
Пошаговое объяснение:
3)
(3x-1)/3≤(x+4)/2+1 |×6
2*(3x-1)≤3*(x+4)+6
6x-2≤3x+12+6
3x≤20 |÷3
x=6²/₃
Ответ: 1, 2, 3, 4, 5, 6.
4)
x+(6x+20)/15≤(2+6x)/5+2 |×15
15x+6x+20≤3*(2+6x)+30
21x+20≤6+18x+30
21x+20≤18x+36
3x≤16 |÷3
x≤5¹/₃
Ответ: 1, 2, 3, 4, 5.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
3)
(3x-1)/3≤(x+4)/2+1 |×6
2*(3x-1)≤3*(x+4)+6
6x-2≤3x+12+6
3x≤20 |÷3
x=6²/₃
Ответ: 1, 2, 3, 4, 5, 6.
4)
x+(6x+20)/15≤(2+6x)/5+2 |×15
15x+6x+20≤3*(2+6x)+30
21x+20≤6+18x+30
21x+20≤18x+36
3x≤16 |÷3
x≤5¹/₃
Ответ: 1, 2, 3, 4, 5.